Pengaruh Kompetensi Terhadap Beban Kerja Pada Perawat Rawat Inap di Rsud I.A Moeis Samarinda - Intan Nur Azizah; Nurhasanah Nurhasanah; M. Ardan (Jurnal Ners, 2026)
Based on the data obtained regarding the workload experienced by nurses, nurse workload is a real problem at I.A. Moeis Regional General Hospital Samarinda. This condition occurs when in one shift, 6 nurses handle up to 40 patients or more. As many as 67% of nurses stated that the workload is in the heavy category. This condition triggers work fatigue and risks reducing the quality of service and patient safety. One factor suspected of influencing workload is nurse competence in carrying out clinical tasks, communication, and nursing care management. Low competence can slow down actions, increase work errors, and increase work pressure in the inpatient ward. This study aims to analyze the effect of competence on the workload of inpatient nurses using quantitative methods with a cross-sectional design on 91 respondents through a purposive sampling technique. Data collection used a questionnaire that has been tested for validity and reliability and analyzed using the Spearman Rank test. The correlation test showed an r value of 0.001 with a p value of 0.993. Thus, the results of the study show that the null hypothesis (H₀) is accepted, which means that there is no significant influence of competence on the workload of inpatient nurses at I.A Moeis Regional General Hospital, Samarinda.